VD_FINDINFO 38/2010/PHC vom 5. März 2010 - VD Tribunal cantonal (2010)
HYPOTHÈQUE LÉGALE DES ARTISANS ET ENTREPRENEURS, GAGE COLLECTIF, CALCUL DU DÉLAI | 818 CC, 837 al. 1 ch. 3 CC, 839 al. 2 CC, 839 CC, 961 al. 3 CC, 3 CPC